The Yankee International: Marxism and the American Reform Tradition, 1848-1876 - Buhle, Paul (Labour / Le Travail, 1999)
The article reviews the book, "The Yankee International: Marxism and the American Reform Tradition, 1848-1876," by Timothy Messer-Kruse.

Schooling for "Good Rebels": Socialist Education for Children in the United States, 1900-1920 - Buhle, Paul (Labour / Le Travail, 1993)
The article reviews the book, "Schooling for "Good Rebels": Socialist Education for Children in the United States, 1900-1920," by Kenneth Teitelbaum.

The New York Intellectuals: The Rise and Decline of the Anti-Stalinist Left from the 1930s to the 1960s - Buhle, Paul (Labour / Le Travail, 1989)
The article reviews the book, "The New York Intellectuals: The Rise and Decline of the Anti-Stalinist Left from the 1930s to the 1960s," by Alan Wald.
Keywords: GENERATION of Boomers: The Pattern of Railroad Labor Conflict in 19th-Century America, A (Book); LABOR market; Nonfiction; REVIEWS; STROMQUIST, Shelton; books

Tremors of Discontent: My Life in Print 1970-1988 - Buhle, Paul (Labour / Le Travail, 2022)
The article reviews the book, "Tremors of Discontent: My Life in Print 1970-1988," by Mike Richardson.
Keywords: MEMOIRS; NONFICTION; RICHARDSON, Mike; TREMORS of Discontent: My Life in Print 1970-1988 (Book)